A multi-technique study of altered granitic rock from the Krunkelbach Valley uranium deposit, Southern Germany. Issue 43 (6th July 2020) - Pidchenko, Ivan; Bauters, Stephen; Sinenko, Irina; Hempel, Simone; Amidani, Lucia; Detollenaere, Dirk; Vinze, Laszlo; Banerjee, Dipanjan; van Silfhout, Roelof; Kalmykov, Stepan N.; Göttlicher, Jörg; Baker, Robert J.; et al.
Abstract : A multi-technique elemental and microphase analysis of altered granitic rock from the Krunkelbach Valley uranium deposit, Black Forest, Southern Germany. Abstract : Herein, a multi-technique study was performed to reveal the elemental speciation and microphase composition in altered granitic rock collected from the Krunkelbach Valley uranium (U) deposit area near an abandoned U mine, Black Forest, Southern Germany. The former Krunkelbach U mine with 1–2 km surrounding area represents a unique natural analogue site with the rich accumulation of secondary U minerals suitable for radionuclide migration studies from a spent nuclear fuel (SNF) repository. Based on a micro-technique analysis using several synchrotron-based techniques such as X-ray fluorescence analysis, X-ray absorption spectroscopy, powder X-ray diffraction and laboratory-based scanning electron microscopy and Raman spectroscopy, the complex mineral assemblage was identified. While on the surface of granite, heavily altered metazeunerite–metatorbernite (Cu(UO2 )2 (AsO4 )2− x (PO4 ) x ·8H2 O) microcrystals were found together with diluted coatings similar to cuprosklodowskite (Cu(UO2 )2 (SiO3 OH)2 ·6H2 O), in the cavities of the rock predominantly well-preserved microcrystals close to metatorbernite (Cu(UO2 )2 (PO4 )2 ·8H2 O) were identified. The Cu(UO2 )2 (AsO4 )2− x (PO4 ) x ·8H2 O species exhibit uneven morphology and varies in its elemental composition, depending on the microcrystal part ranging from well-preserved to heavily altered on a scale of ∼200 μm. The microcrystal phase alteration could be presumably attributed to the microcrystal morphology, variations in chemical composition, and geochemical conditions at the site. The occurrence of uranyl-arsenate-phosphate and uranyl-silicate mineralisation on the surface of the same rock indicates the signatures of different geochemical conditions that took place after the oxidative weathering of the primary U- and arsenic (As)-bearing ores. The relevance of uranyl minerals to SNF storage and the potential role of uranyl-arsenate mineral species in the mobilization of U and As into the environment is discussed.